An Analysis of Teacher and Students’ Talk in their Online Public Speaking Class Interaction Via Zoom Cloud Meeting (Qualitative Research) - Nurfitriani, Ine; Faridah, Didih; Rohayati, Dedeh (Journal of English Education Program (JEEP), 2025)
The phenomena of Covid-19 challenges the government in carrying out the classroom activity; for this reason, the government issued a policy to change studying activities which are commonly achieved in the classroom into studying from home throughout the Covid-19. This research discusses teacher and students’ talk in their online public speaking class interaction via zoom cloud meeting. The purpose of this study was aimed to find out the types of teachers and students chatting in their online interaction via zoom cloud meetings, the types of classroom interaction in public speaking class via zoom cloud meetings, and to find out students’ perceptions toward their teacher talk through zoom cloud meeting. The present study used a qualitative paradigm with the type of  intrinsic case study. Thirteen students from a 2C public speaking class in an English education program, and an English lecturer participated in this research. The data taken from observation aims to find out types of teacher and students talk in public speaking class via zoom cloud meeting, and types of classroom interaction in public speaking class. Meanwhile, a set of questionnaires was employed to collect data about the students’ perceptions toward their teacher talk through zoom cloud meeting. The data from observation were proceeded by means of FLINT System to interpret teacher and students' talk; regarding the type of classroom interaction was adapted from Malamah-Thomas (1987 as cited in Alifea Asanuary Sharliz, 2017). The questionnaire data were analyzed using the Likert Scale measurement. The findings revealed that the types of teachers and student talk and the types of classroom interaction that occurred in class 2C were dominated by the teacher talk. Although students prefer to talk a lot in class, the results of this study indicated that the teacher talks more in class. The researcher suggests for the public speaking teacher to make changes in classroom activity for the coming semester, i.e., the teacher facilitates students to talk a lot during the process of teaching and learning.